ANALISIS PEMAHAMAN PERENCANAAN KARIR SISWA DI KELAS XII SMA NEGERI 9 PONTIANAK - Sumita, Sumita; Wicaksono, Luhur; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe problem in this research is how to understanding student career planning in class XII state senior high school 9 Pontianak?.This study aims to obtain objective information about the understanding of carrer planning students in class XII of state senior high school 9 Pontianak. The methodâ€™s used in this research is descriptive method with survey study form. The sample in this research is 55 students. Data collecting technique in this research is indirect communication technique and direct communication technique. The data collection tool in this research is questionnaire. The result of data analysis shows that understanding of carrer planning of state senior high school 9 Pontianak reaching 88,63% into category, â€œvery goodâ€ that is showing the students have understood career planning for in the future. It is expected that students can understand themselves by knowing their talents and interests to make a decision after graduating senior high school by making career planning.Â Keywords: understanding, career planning, High school student